Foraging behaviour of a desert rodent community: habitat or moon – which is more influential?. Issue 4 (1st October 2016) - Roschlau, C.; Scheibler, E.
Abstract : In this field study, we questioned how diverging vegetal coverage, temperature and moonlight influence the patch use indicated by the giving-up density (GUD) of a nocturnal small mammal community in sheltered and non-sheltered food patches. We investigated the foraging strategy of a widely spread community consisting of Desert hamsters ( Phodopus roborovskii ), Midday gerbils ( Meriones meridianus ), Northern three-toed jerboas (Dipus sagitta ) and Long-eared hedgehogs ( Hemiechinus auritus ) in the Alashan Desert, China. The aim was to analyse foraging as a result of biotic and abiotic factors in undisturbed habitats, i.e. we did not manipulate any surrounding conditions and all animals were free ranging. Three habitats were investigated, named after the dominant species: Ammopiptanthus mongolicus, Corispermum sp. and Zygophyllum pterocarpum . The following results can be summarised: (1) we found no or only slight differences for the GUD within the habitats between open and sheltered places; (2) lunar illumination affected foraging during waxing and waning moon phases within the first part of the night; (3) ambient temperature and the presence of moonlight resulted in changes in the interspecific competition that impacted the GUD; and (4) we determined prominent differences amongst habitats within the four moon phases, especially between the more covered habitats Ammopiptanthus and Zygophyllum, in contrast to the Corispermum habitat with its sparse coverage ratio. In general, foraging effort was elevated in the more covered habitats. We found a preferred foraging activity in warm and dark parts of the night which may lead to elevated inter-individual competition resulting in higher GUDs. Warmer periods were preferred in nights with constant light conditions, although resource competition was again elevated. We concluded that the foraging strategy was mainly affected by habitat, whereas moonlight and temperature modulate the resulting GUD in undisturbed environments. The availability of vegetal shelters influences foraging only in detail.